2021
DOI: 10.1039/d1ma00535a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework thin films as versatile chemical sensing materials

Abstract: Metal-organic frameworks (MOFs) have been widely investigated as chemical sensing materials due to their periodic porosity, tunable chemical functionalities such as Lewis acid/base sites, potential conductivity and/or sensitive optical properties....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 253 publications
0
47
0
1
Order By: Relevance
“…There was also less detachment of PANI from the films produced by this technique; as such, the direct growth of PANI on the film is a better alternative as it offers higher uniformity of attachment for a longer time. Similarly, a recent review by Ellis et al [27] reported that the advantage of the in-situ over ex-situ synthesis technique is the adhesion strength of the coating layer on the substrate.…”
Section: Surface Properties Of Pani Multilayer Firm Formed Via In-sit...mentioning
confidence: 95%
“…There was also less detachment of PANI from the films produced by this technique; as such, the direct growth of PANI on the film is a better alternative as it offers higher uniformity of attachment for a longer time. Similarly, a recent review by Ellis et al [27] reported that the advantage of the in-situ over ex-situ synthesis technique is the adhesion strength of the coating layer on the substrate.…”
Section: Surface Properties Of Pani Multilayer Firm Formed Via In-sit...mentioning
confidence: 95%
“…[33][34][35][36][37] However, unlike sensing in liquid media, the preparation of a MOF-based gas sensor is a challenging task because it requires an optically inert platform able to support the MOF crystals and to provide good accessibility of the cages to the incoming gaseous analyte. 38 In this sense, embedment of the MOF crystals into thin films of polymeric matrices has shown to be a practical and useful approach for this goal. 39,40 Focusing on gas sensors exhibiting improved sensitivity and selectivity towards target analytes that are very important for the protection of the society from toxic pollutants and terrorist attacks, polymeric films including RE 3+ -MOFs have been used to detect a number of molecular species including explosives, 15 NO 2 16 and VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In particular for sensing applications, the fabrication of MOFs as thin films enhance their pore orientation control, and their integration into electronic devices. [4][5][6] The synthesis procedures of high-quality oriented MOF thin films are already well-established. 7 In order to control MOF growth direction for pore orientation on the film, the substrate surface usually needs to be functionalised.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 In particular for sensing applications, the fabrication of MOFs as thin films enhance their pore orientation control, and their integration into electronic devices. 4–6…”
Section: Introductionmentioning
confidence: 99%